2018
DOI: 10.1109/tsp.2018.2868314
|View full text |Cite
|
Sign up to set email alerts
|

An Iterative Receiver for OFDM With Sparsity-Based Parametric Channel Estimation

Abstract: In this work we design a receiver that iteratively passes soft information between the channel estimation and data decoding stages. The receiver incorporates sparsity-based parametric channel estimation. State-of-the-art sparsity-based iterative receivers simplify the channel estimation problem by restricting the multipath delays to a grid. Our receiver does not impose such a restriction. As a result it does not suffer from the leakage effect, which destroys sparsity. Communication at near capacity rates in hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
(150 reference statements)
0
9
0
Order By: Relevance
“…This can be expressed as Figure 3, whereby the fluctuation range of the optimal value of γ corresponding to different R and f d are indicated by the vertical bars. Noted that the optimal value of γ simulated in Figure 3 (solid line) is obtained by searching step by step with step length 0.1 according to Equation (22). It can be observed that there is an approximate Symmetry 2019, 11, 997 9 of 20 exponential function relationship between γ and R, and the exponential curve shifts up and down with the increase and decrease of f d .…”
Section: Determine the Average Frames Adaptivelymentioning
confidence: 93%
See 4 more Smart Citations
“…This can be expressed as Figure 3, whereby the fluctuation range of the optimal value of γ corresponding to different R and f d are indicated by the vertical bars. Noted that the optimal value of γ simulated in Figure 3 (solid line) is obtained by searching step by step with step length 0.1 according to Equation (22). It can be observed that there is an approximate Symmetry 2019, 11, 997 9 of 20 exponential function relationship between γ and R, and the exponential curve shifts up and down with the increase and decrease of f d .…”
Section: Determine the Average Frames Adaptivelymentioning
confidence: 93%
“…Combining channel soft information and Turbo decoding in an iterative way can greatly improve the accuracy of channel estimation, which can be realized by the expectation maximization (EM) algorithm or belief propagation (BP) algorithm [21,22]. In [22], an iterative channel estimation based on a factor graph is proposed; this method iteratively passes soft information between the channel estimation and data decoding stages through the BP algorithm. The main disadvantage of this method is the high computational complexity caused by multiple iterations.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations